A dental perspective on the successes and limitations of the disaster victim identification response to the Nepal earthquake - Samarika Dahal; Gopal Kumar Chaudhary; Mani Raj Maharjan; Eugen Dolma Walung (Oxford University Press, 2022)
This article describes the forensic odontological analysis of the events of the 2015 Nepal earthquake. It identifies the problems encountered in the aftermath, lessons learned, and prospective future advances aimed at reducing the subjectivity in disaster victim identification (DVI). During a crisis, dental practitioners, particularly forensic odontologists, can make a substantial contribution to DVI, as highlighted in this article. It also promotes best practices in forensic dentistry that may be used by anyone in situations with few resources or people to deal with comparable scenarios.